Trust and Engagement on Twitter During the Management of COVID-19 Pandemic: The Effect of Gender and Position - Yousefinaghani, Samira; Dara, Rozita; MacKay, Melissa; Papadopoulos, Andrew; Sharif, Shayan (Frontiers in Sociology, 2022)
During the COVID-19 pandemic, health and political leaders have attempted to update citizens using Twitter. Here, we examined the difference between environments that social media has provided for male/female or health/political leaders to interact with people during the COVID-19 pandemic. The comparison was made based on the content of posts and public responses to those posts as well as user-level and post-level metrics. Our findings suggest that although health officers and female leaders generated more contents on Twitter, political leaders and male authorities were more active in building networks. Offensive language was used more frequently toward males than females and towards political leaders than health leaders. The public also used more appreciation keywords toward health leaders than politicians, while more judgemental and economy-related keywords were used toward politicians. Overall, depending on the gender and position of leaders, Twitter provided them with different environments to communicate and manage the pandemic.